2014
DOI: 10.1039/c4cp01961j
|View full text |Cite
|
Sign up to set email alerts
|

Long-life Na–O2 batteries with high energy efficiency enabled by electrochemically splitting NaO2 at a low overpotential

Abstract: Metal-air batteries are thought to be the ultimate solution for energy storage systems owing to their high energy density. Here we report a long-life Na-O2 battery with a high capacity of 750 mA h g(carbon)(-1) by manipulating the nucleation and growth of nano-sized NaO2 particles in a vertically aligned carbon nanotubes (VACNTs) network with a large surface area. Benefiting from the kinetically favorable formation of NaO2 reaction with a low overpotential of ~0.2 V, the electrical energy efficiency is as high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
179
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(195 citation statements)
references
References 34 publications
14
179
0
2
Order By: Relevance
“…The results in regards to the electrochemical Na−O 2 reactions (2.26 V for NaO 2 and 2.33 V for Na 2 O 2 under pure oxygen) are consistent with the values calculated in previous reports, 12,13,25 while the corresponding EMFs have a slight difference when changed from pure oxygen to simulated air (20% O 2 ). However, the EMFs for electrochemical formation of NaOH (4Na + + 4e + 2H 2 O(g) + O 2 (g) → 4 NaOH(s)) varied from 2.63 to 2.58 V, assuming that the air's RH ranges from 100% to 1% at 25°C.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The results in regards to the electrochemical Na−O 2 reactions (2.26 V for NaO 2 and 2.33 V for Na 2 O 2 under pure oxygen) are consistent with the values calculated in previous reports, 12,13,25 while the corresponding EMFs have a slight difference when changed from pure oxygen to simulated air (20% O 2 ). However, the EMFs for electrochemical formation of NaOH (4Na + + 4e + 2H 2 O(g) + O 2 (g) → 4 NaOH(s)) varied from 2.63 to 2.58 V, assuming that the air's RH ranges from 100% to 1% at 25°C.…”
Section: Resultssupporting
confidence: 94%
“…In contrast, it has recently been experimentally proven that the NaOH phase can be decomposed around 3.15 V in SABs. 25 It is also worthy to note that Kang's group recently reported that the decomposition energy barrier for Na 2 O 2 and NaO 2 are theoretically calculated to be lower than Li 2 O 2 . 20 Thus, the difference between the decomposition of sodium and lithium hydroxides may be further explained based on theoretical calculation or subsequent experiments in future.…”
Section: Resultsmentioning
confidence: 98%
“…This highlights again the sensitivity of NaO 2 oxidation to electrolyte reactivity, vide infra. We propose that the plateau at 3.20 V vs. Na/Na + found in the PITT measurements corresponds to oxidation of NaOH (thermodynamic potential of NaOH Solid is 3.11 V vs. Na/Na + ) 18 . The decomposition of NaOH has been observed at 3.15V vs. Na/Na + by Zhao et al and was related to the decomposition of Na 2 O 2 .2H 2 O→ 2NaOH + H 2 O + 1/2O 2 .…”
mentioning
confidence: 85%
“…The decomposition of NaOH has been observed at 3.15V vs. Na/Na + by Zhao et al and was related to the decomposition of Na 2 O 2 .2H 2 O→ 2NaOH + H 2 O + 1/2O 2 . 18 In order to examine the effect of NaO 2 -electrolyte exposure time on the charging kinetics, we discharged Na-O 2 cells to 500 mAh/g c at rates of 1000 and 10 mA/g c ( Figure 2) and aged them in contact with the electrolyte at OCV from 1 to 20 days, followed by charging at a galvanostatic rate of 100 mA/g c . For electrodes discharged at 1000 and 10 mA/g c , aging up to 20 days led to significant loss in the charging capacity for the low-voltage plateau (<3.00 V vs. Na/Na + ) characteristic of NaO 2 oxidation.…”
mentioning
confidence: 99%
“…[5][6][7][8] Inspired by the complex by-product formation reactions at the cathode side of Li-O 2 batteries, 5 most of the research studies have been focused on the characterization of cathodes, e.g., effects of cathode morphology and by-products on cyclability. 7 However, McCloskey et al pointed out that the cleaner cathode reactions in Na-O 2 compared to Li-O 2 were less concerned and the low cycle life was perhaps caused by the Na anode. 6 Zhao et al detected sodium hydroxide and sodium carbonate as decomposition products on vertically aligned carbon nanotubes.…”
mentioning
confidence: 99%